Islamic banking system – conscientious revelation of credit risk - Cheang, Siau Hui; Choong, Suan Yeng; Yap, Queenie Chia Yee; Teoh, Geik Tao; Wong, Shu Qi (2022)
The aim of this study is to investigate the relationship of Islamic banks’ governance and some specific factors to the defaulting risk in Islamic banking industry from year 2010 to 2019. The variables of Islamic banks’ governance are bank specific factors, corporate governance factors, Shariah governance factors, audit factors and macroeconomics factors. Additionally, we used panel data in this study and data collection is based on annual basis from 2010 to 2019. We have been accessing to Islamic banks’ annual report, banks’ website, and world bank data to gather the data. We have decided to form our samples from 59 Islamic banks in the world. From this study, we have proved that our independence variables which are stated above have a significant relationship with the credit risk of Islamic banks.